2013
DOI: 10.1080/09593330.2013.848910
|View full text |Cite
|
Sign up to set email alerts
|

Greenhouse gas emissions from stabilization ponds in subtropical climate

Abstract: Waste stabilization ponds (WSPs) are a cost-efficient method to treat municipal and non-toxic industrial effluents. Numerous studies have shown that WSPs are a source of greenhouse gas (GHG). However, most reports concerned anaerobic ponds (AP) and few have addressed GHG emissions from facultative (FP) and aerobic/maturation ponds (MPs). In this paper, GHG emissions from three WSP in series are presented. These WSPs were designed as anaerobic, facultative and aerobic/maturation and were treating agricultural w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 30 publications
0
10
0
1
Order By: Relevance
“…In general, wastewater treatment processes contribute to 5 % of the greenhouse gas production in the world, where anaerobic treatment methods are the most responsible (Cakir and Stenstrom 2005). According to Hernandez- Paniagua et al (2014), stabilization ponds typically emit 85 g/m 2 day of CO 2 and 86 g/m 2 day of CH 4 , with nitrous oxide levels significantly lower. In fact, methane emissions in a waste stabilization pond were reported to be twice as high compared to activated sludge systems (HernandezPaniagua et al 2014).…”
Section: Greenhouse Gas Emissionsmentioning
confidence: 99%
“…In general, wastewater treatment processes contribute to 5 % of the greenhouse gas production in the world, where anaerobic treatment methods are the most responsible (Cakir and Stenstrom 2005). According to Hernandez- Paniagua et al (2014), stabilization ponds typically emit 85 g/m 2 day of CO 2 and 86 g/m 2 day of CH 4 , with nitrous oxide levels significantly lower. In fact, methane emissions in a waste stabilization pond were reported to be twice as high compared to activated sludge systems (HernandezPaniagua et al 2014).…”
Section: Greenhouse Gas Emissionsmentioning
confidence: 99%
“…SP are considered by the US Environmental Protection Agency as a source of CH 4 emissions (Todd et al 2011); anaerobic pons are responsible for most of the GHG production in a pond system, with more than 90% of its total emission (Hernandez-Paniagua et al 2013). …”
Section: Introductionmentioning
confidence: 99%
“…In contrast to limited concern about GHG emissions from lakes and reservoirs, their GHG emissions have recently become a research hotspot thanks to growing recognition of their roles in global processes and cycles (Bartosiewicz et al 2015;Wang et al 2017). Plus, it was found that, together with hydropower reservoirs, WSPs produced significantly GHGs as a result of their high inputs of organic matter and nutrients, leading to the elevated emissions (Hernandez-Paniagua et al 2014;Glaz et al 2016).…”
Section: Environment and Ecologymentioning
confidence: 99%